Integration of Importance Performance Analysis (IPA) Method and KANO Model to Measure Customer Satisfaction Level at Bosque Cafe Bungah Gresik - Muhammad Tholhah; Narto (Jurnal Rekayasa Sistem & Industri, 2023)
The Coffee Shop culinary business in the industrial era 4.0 has become a trend among young people. Theexistence of the Covid-19 pandemic requires people to keep their distance and limit activities outside thehome is a challenge in the sustainability of this business, so that these conditions have resulted in adecrease in sales levels. Bosque Café, one of the coffee shop businesses in the city of Gresik, must createquality services to provide comfort in the midst of pandemic conditions and the high business competitionof fellow coffee shops that have been getting higher recently. To attract visitors, several ways must bedone, one of which is to improve the quality of service to customers. The use of the science method to mapthe quality of service with a cartesian diagram can find out the service priorities that must be improved andmaintained. Meanwhile, the KANO model is used for improvement in accordance with the attributes thatmost affect the quality of service. The purpose of this study is to measure the level of customer satisfactionwith the quality of service at Bosque Cafe with an IPA and KANO approach and propose improvements toattributes that affect customer satisfaction. The results of the analysis show that there are 12 serviceattributes that must be improved which are divided into 3 criteria, namely improving human resources,improving services by employees, improving facilities to provide a sense of security and comfort tocustomers